2022
DOI: 10.47760/ijcsmc.2022.v11i11.007
|View full text |Cite
|
Sign up to set email alerts
|

Using Secret Image Block to Secure LSB Data Steganography

Abstract: Data steganography is one of the most popular methods of data protection, but most introduced methods are not secure. In this paper research a simplified LSB method of data steganography will produced, this method will easily used to hide any message in any covering image, changing the image or/and changing the message will not require any changes in the algorithm. The proposed method will use a complicated key to select a secret block from the covering image to be used to hide the message. The PK will contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…An LSB-based hybrid domain has been proposed by K. B. Shiva Kumar et al [24] for steganography, which has been reported to have a higher PSNR and more efficient security compared to other methods. On the other hand, the cryptography technique introduced by Pooja Rani et al [25] involves image steganography, which renders secret message contents unclear to unauthorized users. As mentioned earlier, the basis of steganography is to conceal data through their embedding into a different cover medium.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An LSB-based hybrid domain has been proposed by K. B. Shiva Kumar et al [24] for steganography, which has been reported to have a higher PSNR and more efficient security compared to other methods. On the other hand, the cryptography technique introduced by Pooja Rani et al [25] involves image steganography, which renders secret message contents unclear to unauthorized users. As mentioned earlier, the basis of steganography is to conceal data through their embedding into a different cover medium.…”
Section: Literature Reviewmentioning
confidence: 99%